Pengetahuan orang tua tentang SDIDTK terhadap pelaksanaan stimulasi deteksi dan intervensi dini tumbuh kembang (SDIDTK) Anak Usia 0-23 Bulan - Yanti, Linda Timor; Fauziah, Nur Alfi; Veronica, Septika Yani; Febriyanti, Hellen (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Stimulasi Deteksi dan Intervensi Dini Tumbuh Kembang (SDIDTK) implementation for children under two years old in the village of Kuripan is 35 percent (out of 117 under two years) in 2018 and the lack of attention and knowledge of parents in the need for the importance of SDIDTK. The purpose research was to determine the correlation between parents’ knowledge about SDIDTK to the Implementation of Detection Stimulation and Early Intervention of Growth and Development (SDIDTK) on under-aged children in Kuripan village on Working Area of Inpatient Public Health Center of Penengahan, Penengahan district South Lampung in 2019. The design of this research is Correlative Analytics with a cross-sectional approach. The population in this study are parents who have children under two years old in the village of Kuripan Penegahan district South Lampung in 2018 numbering 117 people, a sample of 117 people with a total sampling technique analysis of data used in this study was univariate data analysis using percentage and bivariate using Chi-Square. The results showed that there was a relationship between parents' knowledge about SDIDTK and the implementation of SDIDTK in children under two years old in the village of Kuripan Penengahan district South Lampung (p-value 0,001) and OR 5,246.